2012
DOI: 10.1165/rcmb.2011-0095oc
|View full text |Cite
|
Sign up to set email alerts
|

Acidic Mammalian Chitinase Is Not a Critical Target for Allergic Airway Disease

Abstract: The expression of acidic mammalian chitinase (AMCase) is associated with Th2-driven respiratory disorders. To investigate the potentially pathological role of AMCase in allergic airway disease (AAD), we sensitized and challenged mice with ovalbumin or a combination of house dust mite (HDM) plus cockroach allergen. These mice were treated or not treated with small molecule inhibitors of AMCase, which significantly reduced allergen-induced chitinolytic activity in the airways, but exerted no apparent effect on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 35 publications
4
37
2
Order By: Relevance
“…It has been reported that AMCase-deficient mice did not show dramatic defects after sensitization and challenge with OVA or HDM plus cockroach allergen (39). These results seem to conflict with our observations.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been reported that AMCase-deficient mice did not show dramatic defects after sensitization and challenge with OVA or HDM plus cockroach allergen (39). These results seem to conflict with our observations.…”
Section: Discussioncontrasting
confidence: 99%
“…While we do not observe an increase in overall HDM uptake by pulmonary DCs following blockade of PD-L2 in vivo , it is possible that PD-L2 blockade may subtly regulate the ability of DCs to take up or present specific allergenic peptides. In primary murine tracheal epithelial cells, IL-12 also inhibited the IL-13-induced expression of the genes encoding IL-33, (a Th2-inducing cytokine 45-46 ), AMCase (capable of enhancing allergen-driven IL-13 production 47-48 ), and Fizz1 (capable of inducing airway eosinophilia and airway remodeling 49 ). We also see reduced IL-13-driven expression of Sprr2b following IL-12 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Age-matched 10-to 14-wk-old female BALB/c mice received a single intratracheal instillation of saline or 100 mg of house dust mite (HDM) extract from Dermatophagoides pteronyssinus (Greer Laboratories, Lenoir, NC) resuspended in saline using a 100-ml Hamilton glass syringe, as previously described (29). Animals were dosed by oral gavage with saline (vehicle), 2 mg/kg dexamethasone (Dex) USP (Sigma-Aldrich), or 200 mg/kg CP-456,773, twice daily, on the day before and the day of HDM challenge.…”
Section: Murine Model Of Acute House Dust Mite Challengementioning
confidence: 99%